Evaluasi rel dan bantalan berdasarkan beban angkut lintas dan kinerja operasi kereta api (studi kasus: jalan rel Tanjung Karang-Rejosari) - Andry Yuliyanto; Galih Rio Prayogi; Michael; Frans Dermanto Hutabarat; Muhammad Abi Berkah Nadi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2024)
In the railway sector, its development has received quite important attention from the government, especially with the establishment of railways as a national strategic plan. The railway network on the island of Sumatra stretches for 1,544 km, including those operating in Lampung Province which is overseen by Regional Division IV Tanjung Karang. Rail transportation in Lampung province is overseen by Regional Division IV Tanjung Karang. In 2022, train services at Tanjung Karang Station recorded services to 556,219 passengers, this data increased by 150.461% from the previous year. This research is important in order to understand how different cross loads affect the condition of rails and sleepers, train operators can plan more effective maintenance, identify vulnerable points, and reduce the risk of operational disruption. This research aims to determine the amount of cross haul loads annually and what is the condition of the ability of rail services and sleepers to accept the traffic loads on them and the impact on operational performance, especially on the realization of train trip scheduling. This research uses a descriptive quantitative method, namely evaluating the condition of the railroad based on secondary data obtained from related agencies. The results of this research show that the Tanjung Karang-Rejosari railroad is categorized as class I railroad, the condition of the installed rails is not in accordance with standards because the basic stress of the rail exceeds the basic stress permitted, so it is necessary to upgrade the rail from R.54 to R.60, to the current condition of the installed bearings is good to serve the annual traffic loads that occur. The operational realization of train travel schedules for both arrival and departure times has been well programmed based on the maximum planned delay time limit. In general, train delays in Regional Division IV Tanjung Karang generally originate from the infrastructure aspect with the percentage of causes of delays being 81.49%. This value illustrates that aspects of railroad infrastructure or structure are the biggest contributor to train delays.